2021
DOI: 10.1002/its2.70
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation frequencies and reference evapotranspiration replacement affecting annual bluegrass encroachment in perennial ryegrass in western Oregon

Abstract: Annual bluegrass (Poa annua L.) encroachment may increase when turfgrass is maintained with excessive irrigation; however, with proper deficit irrigation, annual bluegrass germination and growth may be suppressed while desirable turfgrass is sustained. The goal of this project was to determine the optimal irrigation regime for suppressing annual bluegrass in perennial ryegrass (Lolium perenne L.) stands during the summer months. Two frequencies (once or four times a week) and rates (45% and 80% reference evapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Extension specialists or stakeholders in the cool‐season turfgrass zone would benefit most from research conducted by Cain et al. (2021), Kowalewski et al. (2022), and McNally et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extension specialists or stakeholders in the cool‐season turfgrass zone would benefit most from research conducted by Cain et al. (2021), Kowalewski et al. (2022), and McNally et al.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are similar to results produced by Brosnan et al (2022) in which the vast majority of survey respondents identified creeping bentgrass as the dominant turfgrass on putting greens across the United States. Extension specialists or stakeholders in the cool-season turfgrass zone would benefit most from research conducted by Cain et al (2021), Kowalewski et al (2022), andMcNally et al (2023), which specifically explored methods to control annual bluegrass within other cool-season turfgrass species. Most of the survey participants from the warm-season zone are managing hybrid ultradwarf bermudagrass greens, while creeping bentgrass greens dominated the responses from the transition zone (Table 2).…”
Section: Core Ideasmentioning
confidence: 99%
“…The point intercept method is a quantitative measure with an established history in plant ecology (Jonasson, 1988), which has been adapted into turfgrass research to measure cover. Adaptations of the point intercept method in turfgrass management include a frame with a grid of strings that is placed on the turfgrass surface (Figure 1; Cain et al., 2021; Gaussoin & Branham, 1989; Inguagiato et al., 2008; Schmid et al., 2017; Wang et al., 2018). Data can, then, visually be collected while looking down at the turfgrass surface at the intercept points.…”
Section: Introductionmentioning
confidence: 99%
“…These various adaptations of the point intercept method have been used to quantify percent cover of mixed stands of perennial ryegrass ( Lolium perenne L.) and annual bluegrass ( Poa annua L.) (Cain et al., 2021), tall fescue ( Schedonorus arundinaceus [Schreb.] Dumort.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation